1996
DOI: 10.1172/jci118575
|View full text |Cite
|
Sign up to set email alerts
|

Activated platelets signal chemokine synthesis by human monocytes.

Abstract: Human blood monocytes adhere rapidly and for prolonged periods to activated platelets that display P-selectin, an adhesion protein that recognizes a specific ligand on leukocytes, P-selectin glycoprotein-1. We previously demonstrated that P-selectin regulates expression and secretion of cytokines by stimulated monocytes when it is presented in a purified, immobilized form or by transfected cells. Here we show that thrombin-activated platelets induce the expression and secretion of monocyte chemotactic protein-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
496
2
12

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 567 publications
(536 citation statements)
references
References 81 publications
26
496
2
12
Order By: Relevance
“…Leukocyte-derived microparticles trigger endothelial cells to produce interleukin-6 (39,40). P-selectin, which is present on platelet-derived microparticles, triggers monocytes to express not only tissue factor, but also chemokines (41,42). Platelet-derived microparticles transport arachidonic acid to endothelial cells and induce the expression of cyclooxygenase 2 and the increased production of prostacyclin (43), enhance the interaction between monocytes and endothelial cells (44), and enhance leukocyte aggregation and their accumulation on the endothelium (45).…”
Section: Discussionmentioning
confidence: 99%
“…Leukocyte-derived microparticles trigger endothelial cells to produce interleukin-6 (39,40). P-selectin, which is present on platelet-derived microparticles, triggers monocytes to express not only tissue factor, but also chemokines (41,42). Platelet-derived microparticles transport arachidonic acid to endothelial cells and induce the expression of cyclooxygenase 2 and the increased production of prostacyclin (43), enhance the interaction between monocytes and endothelial cells (44), and enhance leukocyte aggregation and their accumulation on the endothelium (45).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, however, the main receptors facilitating PLAs (i.e. P-selectin, CD40L, GPIbα, GPVI, GPIIb/IIIa on platelets and PSGL-1, CD40, Mac-1 on leukocytes) are consistently involved in both mice and human (2,4,6,8,3138). …”
Section: Translational Aspects Of Animal Modelsmentioning
confidence: 99%
“…Platelet-leukocyte interactions are further stabilised by crosstalk of numerous additional receptor/ligand pairs that were reviewed previously (1,5) and trigger mutual activation and release of granular content by both platelets and leukocytes, thereby modulating leukocyte function and fine-tuning immune responses (5). Importantly, platelet-leukocyte interactions facilitate leukocyte recruitment and extravasation to sites of inflammation (6,7), promote leukocyte release of pro-inflammatory mediators (8,9), oxidative burst, phagocytosis, release of neutrophil extracellular traps (NETs) (10,11), and may also dampen inflammation under some pathological conditions (1214). …”
Section: Introductionmentioning
confidence: 99%
“…In parallel, endothelial PAF has been implicated in juxtacrine stimulation of integrin function in PMN tethered through P-selectin on thrombin-stimulated endothelium (54). Although P-selectin itself does not trigger arrest of PMN under flow, it may cooperate with chemoattractants to stimulate leukocytes (55). It has recently been confirmed that PMN adhesion on immobilized platelets under shear flow requires both a juxtacrine activation mechanism involving PAF and an enhancing signal from P-selectin (56).…”
Section: Involvement Of Platelet-activating Factor (Paf) and Leukotrimentioning
confidence: 99%